2017
DOI: 10.1371/journal.pone.0179640
|View full text |Cite
|
Sign up to set email alerts
|

Functional metabolomics as a tool to analyze Mediator function and structure in plants

Abstract: Mediator is a multiprotein transcriptional co-regulator complex composed of four modules; Head, Middle, Tail, and Kinase. It conveys signals from promoter-bound transcriptional regulators to RNA polymerase II and thus plays an essential role in eukaryotic gene regulation. We describe subunit localization and activities of Mediator in Arabidopsis through metabolome and transcriptome analyses from a set of Mediator mutants. Functional metabolomic analysis based on the metabolite profiles of Mediator mutants usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In Arabidopsis, several functions have been reported for the different subunits integrating this complex (Zheng et al ., ; Samanta and Thakur, ; Fallath et al ., ). Although such functions must be interconnected, subunits that integrate the same Mediator module seem to participate in the same biological process (Davoine et al ., ). MED18 belongs to the head‐module Mediator complex that was originally identified as a general transcription factor that stimulates basal RNA Polymerase II transcription in yeast (Kornberg, ; Larivière et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In Arabidopsis, several functions have been reported for the different subunits integrating this complex (Zheng et al ., ; Samanta and Thakur, ; Fallath et al ., ). Although such functions must be interconnected, subunits that integrate the same Mediator module seem to participate in the same biological process (Davoine et al ., ). MED18 belongs to the head‐module Mediator complex that was originally identified as a general transcription factor that stimulates basal RNA Polymerase II transcription in yeast (Kornberg, ; Larivière et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis was supported by the discovery of two A. thaliana phospholipases, pPLAIIa and AtPLAI, able to release free OPDA from oxidized glycolipids (Yang et al 2007(Yang et al , 2012. In the same way, arabidopside levels are increased in some A. thaliana mutants with reduced pPLAIIa expression (Davoine et al 2017). (dn)OPDA containing MGMG and DGMG found in, for example, A. thaliana were proposed as by-products formed after free oxylipins hydrolysis from oxidized MGDG and DGDG (Glauser et al 2008).…”
Section: Indirect Functions Of Esterified Oxylipinsmentioning
confidence: 90%
“…MED25 was recently shown to directly link the JA receptor CORONATINE INSENSITIVE 1 (COI1) with promoters of MYC2 target genes, leading to degradation of JAZ-domain transcriptional repressors, HAC1-dependent H3K9 acetylation, and activation of JA-associated target genes 30 . MED16, MED18 and CDK8 have all been shown to interact physically with MED25 [86][87][88] . We found that stress-induced expression of a high proportion of JA-associated genes was dysregulated in med9, med16 and cdk8.…”
Section: Discussionmentioning
confidence: 99%